Mdivi-1 Protects CD4+ T Cells against Apoptosis via Balancing Mitochondrial Fusion-Fission and Preventing the Induction of Endoplasmic Reticulum Stress in Sepsis. (16th May 2019) - Wu, You; Yao, Yong-Ming; Ke, He-Liang; Ying, Lan; Wu, Yao; Zhao, Guang-Ju; Lu, Zhong-Qiu
Abstract : Apoptosis of CD4 + T cells plays a central role in the progression of sepsis because it is associated with subsequent immunosuppression and the lack of specific treatment. Thus, developing therapeutic strategies to attenuate the apoptosis of CD4 + T cells in sepsis is critical. Several studies have demonstrated that Mdivi-1, which is a selective inhibitor of the dynamin-related protein 1 (Drp1), attenuates apoptosis of myocardial cells and neurons during various pathologic states. The present study revealed the impact of Mdivi-1 on the apoptosis of CD4 + T cells in sepsis and the potential underlying mechanisms. We used lipopolysaccharide (LPS) stimulation and cecal ligation and puncture (CLP) surgery as sepsis models in vitro and in vivo, respectively. Our results showed that Mdivi-1 attenuated the apoptosis of CD4 + T cells both in vitro and in vivo . The potential mechanism underlying the protective effect of Mdivi-1 involved Mdivi-1 reestablishing mitochondrial fusion-fission balance in sepsis, as reflected by the expression of the mitofusin 2 (MFN2) and optic atrophy 1 (OPA1), Drp1 translocation, and mitochondrial morphology, as observed by electron microscopy. Moreover, Mdivi-1 treatment reduced reactive oxygen species (ROS) production and prevented the induction of endoplasmic reticulum stress (ERS) and associated apoptosis . After using tunicamycin to activate ER stress, the protective effect of Mdivi-1 on CD4 + T cells was reversed. Our results suggested that Mdivi-1 ameliorated apoptosis in CD4 + T cells by reestablishing mitochondrial fusion-fission balance and preventing the induction of endoplasmic reticulum stress in experimental sepsis.